TRADISI BARA’AN DALAM MASYARAKAT DESA TELUK PAMBANG KECAMATAN BANTAN KABUPATEN BENGKALIS - Pebri Karisma; Muhammad Razif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Pambang bay village is located in the District Rural Bantan Bengkalis and includedinto the Malay cultural social, Pambang in Bay Village, there is a unique tradition istradition Bara'an are held once a year just in the celebration of Eid, is the originBara'an words from Malay language meaning